2019
DOI: 10.4186/ej.2019.23.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Moment Capacity Evaluation of Reinforced RPC Two-way Slabs

Abstract: The aim of this paper is to determine the flexural moment capacity of Reactive Powder Concrete (RPC) two-way slabs based on three models proposed by previous studies (Model 1, Model 2, and Model 3). The results obtained from these models were compared with those obtained from experimental work to check the accuracy and the applicability of the adopted theoretical models. The experimental program included the testing of three simply supported RPC two-way slabs (1000x1000x70) mm each. The tested specimens had id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The optimum proposed pozzolanic material (CG20) was utilized as partial volumetric replacement from silica fume content at fractions of (5 %, 10 %, 15 %, 20 %, and 25 %). The proportion mix of control mix was stand on earlier local studies mixes [30][31][32][33][34][35]. The quantities of ingredients for mixes in this study are itemized in Table 1.…”
Section: Proportionmentioning
confidence: 99%
“…The optimum proposed pozzolanic material (CG20) was utilized as partial volumetric replacement from silica fume content at fractions of (5 %, 10 %, 15 %, 20 %, and 25 %). The proportion mix of control mix was stand on earlier local studies mixes [30][31][32][33][34][35]. The quantities of ingredients for mixes in this study are itemized in Table 1.…”
Section: Proportionmentioning
confidence: 99%
“…To solve this problem, steel fibers are usually added to improve ductility [6]. Many studies collectively demonstrated that adding steel fibers to RPC can significantly improve its mechanical properties, including compressive strength, flexural strength, toughness, and crack resistance; moreover, highlighting the positive influence of steel fibers on enhancing the performance and durability of RPC [2,5,[7][8][9][10][11]. Concrete can be made with special mechanical properties to withstand different types of loading and reduce the dead load by reducing the geometrical dimensions and increasing the strength.…”
Section: Introductionmentioning
confidence: 99%